MICRO THERMAL ELASTOHYDRODYNAMIC LUBRICATION ANALYSIS OF LINE CONTACT ROLLER PAIRS CONSIDERING THE CHANGE OF ELASTIC MODULUS - LU ZunYou; LV YanJun (Jixie qiangdu)
As an important performance parameter of metal materials,the elastic modulus changes with temperature.However,in the analysis of thermal elastohydrodynamic lubrication,the elastic modulus has been taken as a constant,and there must be an error in the calculation results. Taking the infinitely long line contact roller pair as the research object,the relationship between the change of solid elastic modulus and temperature was introduced into the theory of thermal elastohydrodynamic lubrication, combined with the theory of thermoelastic mechanics and the principle of heat-pressure conversion,a numerical calculation method considering the effect of random roughness was presented. The calculation of the elastic modulus field was added to the calculation,and the convergence accuracy of the elastic modulus field was set. The calculation was carried out through an example,and the influence of the load change was analyzed before and after considering the change of elastic modulus. The research content can provide a theoretical basis for the analysis of elastohydrodynamic lubrication and material properties.